2008
DOI: 10.1038/bmt.2008.22
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity conditioning allogeneic SCT as salvage treatment for relapsed multiple myeloma

Abstract: The aim of this retrospective analysis was to assess the benefit of reduced-intensity conditioning allo SCT (RIC allo-SCT) in a cohort of 32 relapsed multiple myeloma (MM) patients. A total of 19 patients had an HLAidentical sibling donor ('donor' group), while 13 patients had no donor ('no-donor' group). There were no significant differences between these two groups as for prognosis risk factors. Eighteen patients from the 'donor' group could actually proceed to RIC allo-SCT. With a median followup of 36 (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 38 publications
(46 reference statements)
4
42
0
Order By: Relevance
“…RIC has reduced the NRM to 10% to 20%. [14][15][16][17][18][19][20][21]24,25 A retrospective large study of the EBMT compared outcome after RIC (320 patients) and myeloablative SCT (196 patients). 16 RIC was found to reduce NRM (24% vs 37%), but this rate was offset by an increase in disease recurrence rates (54% vs 27%), resulting in similar OS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RIC has reduced the NRM to 10% to 20%. [14][15][16][17][18][19][20][21]24,25 A retrospective large study of the EBMT compared outcome after RIC (320 patients) and myeloablative SCT (196 patients). 16 RIC was found to reduce NRM (24% vs 37%), but this rate was offset by an increase in disease recurrence rates (54% vs 27%), resulting in similar OS.…”
Section: Discussionmentioning
confidence: 99%
“…NRM was, as may be expected, higher than in the upfront approach, reaching 26%, which is similar to other studies in the same setting. [14][15][16]24,25 With a median follow-up of >6 years, there was a clear plateau in the PFS curve after 3 years, with 34% of patients alive and 26% free of disease progression, 7 years after allogeneic SCT. The EBMT study showed, in a heterogeneous group of 229 patients, similar 3-year OS and PFS rates of 41% and 21%, respectively, with no plateau.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have performed retrospective analyses with conflicting results. De Lavallade et al 45 and Patriarca et al 29 described two retrospective donor vs no donor analyses, finding a superior PFS for patients with a donor, however, no difference in OS, while Karlin et al 30 recently reported an advantage in OS for allogeneic transplant using a propensity score matching method. Finally, a recent abstract described registry data comparing allogeneic vs autologous transplantation as a second transplant following relapse and found a significantly worse PFS and OS for patients who received an allogeneic transplant, 46 however, the groups were not well balanced.…”
Section: Discussionmentioning
confidence: 99%